2005
DOI: 10.1007/s10549-005-9071-1
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-selective retinoids inhibit the growth of normal and malignant breast cells by inducing G1 cell cycle blockade

Abstract: Despite advances in treatment, breast cancer continues to be the second leading cause of cancer mortality in women. Statistics suggest that while focus on treatment should continue, chemopreventive approaches should also be pursued. Previous studies have demonstrated that naturally occurring retinoids such as 9-cis retinoic acid (9cRA) can prevent breast cancer in animal models. However, these studies have also shown that these compounds are too toxic for general use. Work from our laboratory showed that an RX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
27
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 25 publications
5
27
0
Order By: Relevance
“…The proportion of cells that undergo apoptosis was not increased after 4 months treatment of bexarotene ( Figure 2B). This is consistent with our previous results, in which rexinoid did not promote apoptosis in normal mammary epithelial cells (Wu et al, 2006). Christov et al (2007) found that short-term treatment with high dose of bexarotene (150 mg kg À1 ) induced apoptosis in methylnitrosourea-induced mammary cancers in rat (Christov et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The proportion of cells that undergo apoptosis was not increased after 4 months treatment of bexarotene ( Figure 2B). This is consistent with our previous results, in which rexinoid did not promote apoptosis in normal mammary epithelial cells (Wu et al, 2006). Christov et al (2007) found that short-term treatment with high dose of bexarotene (150 mg kg À1 ) induced apoptosis in methylnitrosourea-induced mammary cancers in rat (Christov et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…This is also supported by our published data showing that the proliferation inhibition by bexarotene was more profound in normal mammary epithelial cells than in breast cancer cells (Wu et al, 2006). Previous studies showed that bexarotene inhibited the breast cancer cell proliferation in vitro (Wu et al, 2002a) and carcinogen-inducted mammary tumour growth in vivo (Bischoff et al, 1999).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations